Personal experiences of elderly Chinese women in a nursing home setting from the existential-humanistic perspective - Lok, Huey Chuen (2010)
This qualitative study aimed at exploring and understanding the personal experiences of elderly Chinese women (ECW) residing in private nursing homes, using the Existential-Humanistic (EH) perspective. The EH perspective sees human beings as comprising the inter-relationships of their physical, social, psychological and spiritual beings. Human beings are also seen as unique and constantly in a process of “becoming”. Every person is free to choose and tends to search for meaning and transcendence or growth in life. Seven elderly Chinese women who voluntarily participated in this study were interviewed using a semi-structured interview guide. Respondents were selected by purposeful sampling from four nursing homes in the Klang Valley. The interview data collected were transcribed verbatim, translated from the Chinese language to English and analyzed using the constant comparative method. Content analysis of the first transcript, field notes and document collected yielded meaningful units or subthemes. Twenty-six subthemes emerged from the analyses of the interview transcripts. These subthemes were further organized into four components of the self according to the EH perspective, namely, physical being, social being, psychological being and spiritual being. Results showed that the ECW participants experienced both positive and negative experiences. ECW participants also hoped for (1) ease of physical pain, (2) social support from family members and friends, (3) having recreational activities, and (4) nurturing others and altruism. The findings primarily showed that the personal experiences of the elderly Chinese women in a nursing home setting is multidimensional and most of them are open to therapeutic talk (interview) where the researcher applied theExistential-Humanistic approach in order to “be present” with them. The findings of the study implied that elderly Chinese women in nursing homes need to fulfill their physical, social, psychological and spiritual dimensions of “self”. EH counseling is deemed suitable for ECW as it is a holistic approach and can help the ECW to transcend physical deterioration through greater self-awareness of their four beings. This approach can also empower elderly Chinese women to live a more authentic life. It offer sopportunities to them to develop their psychological and spiritual dimensions. Future researchers are urged to study the effects of Existential-Humanistic counseling on elderly Chinese women and other ethnic groups.